Senescence patterns of the upper three leaves of rice (Oryza sativa L.) during spikelet filling - Park, T.S; Vergara, B.S; Alejar, Arcelia A. (Asia life sciences :the international journal of life sciences., 1993)
"The leaf senescence of 18 rice varieties was classified according to the rate of chlorophyll loss of the upper three leaves to determine possible correlation between leaf senescence and some morphophysiological characteristics during spikelet filling. Reduction of chlorophyll to about 75% of the initial level (at heading) was observed at 26, 20, and 14 days after heading (DAH) in the flag, penultimate or second, and third leaves, respectively. Decline in chlorophyll content was significant and was positively correlated with decline of photosynthetic activity of flag leaves. Grouped into slow, moderately slow, medium, and rapid senescence types, the measured morphological characters of the different varieties showd no significant differences at maturity. The length, width, and angle of the upper three leaves and culm diameter during spikelet filling were also not significantly different. The senescence-associated decline in leaf area and dry weight was least observed in the slow and moderately slow senescing varieties. Decrease in total dry weight of leaves, stems, and roots of the plant from heading (flowering) to maturity was related, but not at significant levels to senescence type. On the other hand, root respiration rate at 30 DAH in the slow senescing group was higher than that in other types. Results showed that the slow and moderately slow senescence of the upper three leaves contributed to heavier particles and 100 grains."